2011
DOI: 10.4193/rhino10.169
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Management of Acute Rhinosinusitis Among Asian Physicians

Abstract: INTRODUCTIONAcute rhinosinusitis (ARS) is a significant health problem, being one of the top reasons for a visit to primary care clinics (1) . It was found that an average of 8.4 % of the Dutch population reported at least one episode of ARS per year in 1999 (2) . The incidence of visits to the general practitioner for acute rhinosinusitis in the Netherlands in 2000 was 20 per 1000 men and 33.8 per 1000 women (3) . According to data from a National Ambulatory Medical Care Survey (NAMCS) in the USA, rhinosinusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 12 publications
1
34
0
10
Order By: Relevance
“…Viral ARS is one of the most common reasons why patients seek medical advice in ambulatory care. Although clinical studies have demonstrated that antibiotics are not indicated for treatment of viral ARS, antibiotics are still prescribed at high rates while guideline-oriented management suggests symptomatic treatment and reassurance for patients with mild symptoms (1,(5)(6)(7)(8)(9)(10) . Herbal medicinal products containing plant-derived monoterpenes represent a well-tolerated therapeutic option for uncomplicated upper RTIs based on long-standing use, however, the evidence for beneficial effects of herbal compounds for the treatment of viral ARS is limited and there is a real need for more RCTs in this field (1) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral ARS is one of the most common reasons why patients seek medical advice in ambulatory care. Although clinical studies have demonstrated that antibiotics are not indicated for treatment of viral ARS, antibiotics are still prescribed at high rates while guideline-oriented management suggests symptomatic treatment and reassurance for patients with mild symptoms (1,(5)(6)(7)(8)(9)(10) . Herbal medicinal products containing plant-derived monoterpenes represent a well-tolerated therapeutic option for uncomplicated upper RTIs based on long-standing use, however, the evidence for beneficial effects of herbal compounds for the treatment of viral ARS is limited and there is a real need for more RCTs in this field (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Although approximately 98% of ARS are viral and self-limiting, antibiotics are often prescribed in primary care (1,(5)(6)(7)(8)(9)(10)(11) . In fact, only 0.5-2.0% of patients eventually develop acute bacterial rhinosinusitis (ABRS) secondary to a viral infection (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the highest proportion it is provoked by viruses like rhinovirus and coronaviruses but also influenza and parainfluenza, adenovirus, respiratory syncytial virus (RSV), and enterovirus can cause a common cold [1]. In contrast, only 0.5-2% of patients with ARS is estimated to develop acute bacterial sinonasal infection, and this mostly results secondarily to viral RS [4]. In this small proportion of ARS bacteria like S. pneumoniae, H. influenzae, S. aureus, and M. catarrhalis may be detected [5].…”
Section: Causes Of Rhinosinusitis and The Scarce Indications For Antimentioning
confidence: 99%
“…Lately, there have been reported very high incidences as far as acute rhinosinusitis is concerned. It is estimated that adults suffer two to five episodes of viral ARS per year and only 0.5-2% of ARS are complicated by bacteria infection 1,5,6 . Regarding the epidemiology of chronic rhinosinusitis, recent studies show that almost 15% of the population is affected.…”
Section: Introductionmentioning
confidence: 99%